Dental and Oral Health Promotion Program for People with Mental Illness - Pindobilowo; Dwi Ariani; Dhira Mahatidana (Jurnal Multidisiplin Madani, 2022)
Background: More than 450 million people in the world suffer from mental illness in 2017 with mental illness as the biggest contributor to years lived with disabilities. People with mental illness have worse dental and oral health status than the general public. However, this problem is still often ignored by medical personnel who handle it, even though dental and oral health is no less important. One of the things that can be done to overcome this is through the promotion of dental and oral health. Until now, it is not known whether there is a dental and oral health promotion program specifically for people with mental illness and its effectiveness. Purpose: to conduct a literature study that examines the dental and oral health status of people with mental illnesses as well as strategies and effectiveness of dental and oral health promotion for people with mental illnesses. Methods: This literature study uses a narrative review by analyzing various journals from the online databases of BMC Oral Health, PubMed, and Google Scholar which are related to the promotion of oral health and mental illness. Conclusion: This literature study reveals that there are various methods that can be used in promoting oral health for people with mental illness. There are many factors that affect the impact and course of health promotion so that the effectiveness of dental and oral health promotion for people with mental illness still varies. It is necessary to carry out further studies regarding other aspects that play a role as well as other methods that can be used